Demystifying the Hermit Kingdom: the constitution and public administration in North - Jordan, Sara R; Ip, Eric CY (2013)
Background Situations of extreme information deficit regarding administrative behavior are rare, but such conditions persist for the most enigmatic and troubling nations, such as North Korea. How might the behavior of public administrators be explained when systematic observation of individual administrators or institutions' parties is not feasible? Conclusions - While we can better understand the values of administrators in North Korea through constitutional analysis, without harder evidence we can only speculate on the true values of administrators in North Korea. - Reproduced.
Keywords: Public administration